DEPRESSION FOUND IN GREEN DAY’S SELECTED SONGS: “BASKET CASE” AND “BOULEVARD OF BROKEN DREAMS” (PSYCHOLOGICAL APPROACH) - Bata, Levi M; Wanggai, Febe F I; Doi, Maksimilianus (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2024)
This study discusses Depression in the lyrics of the Green Day song. The focus is on the depressive symptoms implied in the lyrics of the songs